2000
DOI: 10.1034/j.1600-065x.2000.17710.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genetic variation in chemokines and their receptorson HIV transmission and progression to AIDS

Abstract: The pivotal discovery that two chemokine receptors, CCR5 and CXCR4, serve along with the T-cell receptor-interacting CD4 molecule as the principal co-receptors for HIV-1 entry stimulated a search for common genetic polymorphism in their genes which might affect the course of AIDS. Four mutational variants, CCR5-delta32, CCR5-P1, CCR2-641 and SDF1-3'A were discovered to play a regulatory role in HIV-1 infection, in the rate of progression to AIDS or both. Plausible physiological mechanisms to explain the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
184
1
9

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(198 citation statements)
references
References 106 publications
(204 reference statements)
4
184
1
9
Order By: Relevance
“…Our findings indicated, however, that the killing activity of HIV1 in our model did not depend on the particular genetic make-up of their Env, since effective killing was induced by MuLV-Env pseudotyped HIV1 particles. Thus, because the major genetic difference between X4-tropic and R5-tropic HIV1 isolates concerns their Env, which dictates their coreceptor usage, 63 our findings suggest the possibility that in conditions in which CCR5 is expressed, R5-tropic HIV1s might induce the same CD4 þ T-cell killing process as X4-tropic HIV1s, when in the presence of dying cells. Assessing whether this is indeed the case might have important implications for our understanding of AIDS pathogenesis.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our findings indicated, however, that the killing activity of HIV1 in our model did not depend on the particular genetic make-up of their Env, since effective killing was induced by MuLV-Env pseudotyped HIV1 particles. Thus, because the major genetic difference between X4-tropic and R5-tropic HIV1 isolates concerns their Env, which dictates their coreceptor usage, 63 our findings suggest the possibility that in conditions in which CCR5 is expressed, R5-tropic HIV1s might induce the same CD4 þ T-cell killing process as X4-tropic HIV1s, when in the presence of dying cells. Assessing whether this is indeed the case might have important implications for our understanding of AIDS pathogenesis.…”
Section: Discussionmentioning
confidence: 78%
“…63 In contrast, the R5-tropic HIV1, which use the CCR5 chemokine receptor as a coreceptor for entry into cells, predominate during most of the asymptomatic phase of HIV1 infection. 63 In vivo, CD4 þ T cells express both CCR5 and CXCR4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus has concentrated on the chemokine receptors and chemokines involved in early stages of infection, such as viral binding and entry. Host genetic factors in genes encoding chemokine receptors and their ligands and in HLA class I antigen-presenting molecules have been associated with variation in susceptibility or resistance to HIV-1 infection and in progression to AIDS especially in predominantly white cohorts (for reviews see Michael 1 , O'Brien and Moore 2 and O'Brien et al 3 ). However, their role in African-American cohorts has been minimal because of lower allele frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Significant studies in the past few years have also demonstrated that innate immunity including genetic polymorphisms in host genes can affect the risk for HIV-1 infection and disease progression (Tab. 1), although the effect of these alleles has been inconsistent [32,[45][46][47][48][49][50][51][52][53][54][55] (reviewed in [56]). Here, we review global and Chinese studies on human genetic polymorphisms and their association with HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%